Socio-environmental analysis in the management of electronic equipament waste and the reverse logistics process at the Court of Justice of Pernambuco – TJPE (Desenvolvimento em Questão, 2024)
This article addresses the importance of reverse logistics as a strategy to guarantee consumption standards and promote sustainable production, as stipulated in the 12th Sustainable Development Goal (SDG 12) of the 2030 Agenda. Furthermore, this research is dedicated to management analysis. electronic waste, evidenced by the promulgation of Law nº 12.305/2010 in the Brazilian legal system. Despite this innovative legislation, the effective implementation of reverse logistics faces challenges, mainly due to a lack of awareness about its importance. Therefore, the objective is to develop a case study carried out at the Court of Justice of Pernambuco (TJPE), with a view to understanding the socio-environmental perceptions and perspectives of two employees in relation to electronic waste processing and reverse logistics. The methodology consists of descriptive research with a qualitative-quantitative approach, which involves the preparation and application of an electronic questionnaire to 207 TJPE employees. The results reveal a significant lack of knowledge about reverse logistics, environmental programs and the TJPE's Sustainable Logistics Plan (PLS). Questionnaire participants demonstrate a lack of familiarity with the corresponding technical terms, as well as a lack of knowledge about the actions promoted by the institution. There is little attention to events related to solid electronic waste and a negative perception regarding the dissemination of appropriate disposal actions. The analysis of two data reveals unsatisfactory results in relation to electronic waste management and reveals the need to implement educational and informative activities, as well as review strategies related to waste management. It is therefore concluded that, to promote sustainable practices and effective waste management, it is essential that two collaborators are incorporated into the perception of environmental policies.
Keywords: Sustainability; Socio-environmental Perception; Sustainable practices; Electronic waste